Induced sputum versus gastric aspirate for microbiological confirmation of pulmonary tuberculosis in infants and young children: A prospective cohort study - Beig, Farzana K.; Ali, Mohd Kashif; Naim, Eeman (Indian Journal of Child Health, 2019)
Introduction: The diagnosis of tuberculosis (TB) is challenging in children due to the paucibacillary nature of disease and difficulty in sample collection. Gastric lavage (GL) is recommended in children because children tend to swallow sputum and do not expectorate; however, it is invasive, stressful and requires admission. Objective: The objective of this study was to compare the yield of GL samples with that of induced sputum, which is a non-invasive method and can be done on an outpatient basis. Methods: A prospective cohort study was done on 55 children, who were <6 years of age, admitted for suspected pulmonary TB (PTB) in Medical College, Aligarh, from December 2011 to December 2013. Sputum induction and GL were done on 3 consecutive days according to the standard procedure. All samples were stained for acid-fast bacilli and each sample was cultured for Mycobacterium tuberculosis. Results: The median age of the children in the study group was 28 months. A positive smear and culture were positive for M. tuberculosis in 7.2% and 20% of children, respectively. There was no significant difference in smear positivity from induced sputum samples compared to gastric aspirate samples. However, the culture positivity for M. tuberculosis was better with induced sputum than gastric aspirate and the difference was statistically significant (p<0.05). Sputum induction procedures were well tolerated; minor side effects were vomiting, mild epistaxis, coughing, or transient wheezing. Conclusion: Sputum induction is safe and useful for microbiological confirmation of TB in young children. This technique is preferable to GL for diagnosis of PTB.